Myocardial Infarction: An analysis of Socio-demographic and Modifiable Risk Factors among Armed Forced Personnel in Bangladesh - Uddin, SM Belal; Mosleh Uddin, Abu Noman Mohammad; Malek, Mohammad Abdul (Anwer Khan Modern Medical College Journal, 2020)
Introduction: Myocardial Infarction, major part of Coronary Artery Disease (CAD) is the leading cause of death for both men and women in the World. In 2008 among all death caused by non-communicable diseases CAD causes more than 27% of death in Bangladesh. Objective: To analyze the socio-demographic and modifiable risk factors of Myocardial Infarction among Armed Forces personnel attended at the Combined Military Hospital Dhaka Methods: This cross sectional study was conducted in July 2012 to Dec 2012 among 104 purposively selected armed forces personnel reported in Combined Military Hospital Dhaka. Data were collected through face-to-face interview using a pretested semi-structured questionnaire. Result: Majority of the respondents (66.3%)age group was 45-60 years and 93.3% were Muslim and most are (69.2%) retired. Smoking rate were 61.5% and almost all of them used to do physical exercise in terms of mild, moderate and strenuous forms (26.0%, 54.8% and 19.2%) respectively. About 62.5% had a history of taking extra salt with food. Almost all of them had several chronic diseases like hypertension, DM and Bronchial Asthma. Conclusion: The study found group of Socio-demographic and modifiable risk factors are responsible for Myocardial Infarction which could be minimized by preventive measures taken by competent authority. Study on larger sample size is necessary for more appropriate description. AKMMC J 2020; 11(2) : 97-101